Studi Literatur: Efektivitas Penggunaan Masker Kain dalam Pencegahan Transmisi COVID-19 - Santy Irene Putri (Jurnal Kesehatan Manarang, 2020)
The government has established a health protocol for the adaptation of new habits, one of which is the use of cloth masks for healthy people. The public's indiscipline with wearing cloth masks as a government preventive effort in preventing the transmission of Covid-19 has led to an increase in Covid-19 cases. The aim of the study was to analyze the literature review on the effectiveness of using cloth masks in preventing the transmission of Covid-19. The research design was a literature review. The search for the articles discussed used several databases, including Pubmed, Ebscohost, Proquest, ScienceDirect, and Wiley Online with a span of 1 January - 29 July 2020. The keywords used to search for these articles were covid-19, coronavirus, 2019 n-cov, coronavirus disease, cloth masks, non-medical masks. The type of article used is a research article. Collected articles were reselected using inclusion criteria, namely: 1) the purpose of the article was to analyze the effectiveness of cloth masks in preventing the transmission of Covid-19, 2) were experimental and qualitative research, and exclusion criteria, namely 1) not a full text article, 2) the article don't use English. After the keyword search process, 13,268 articles were obtained from all databases used. Then the article selection was carried out, 8 articles that met the criteria were selected, 7 articles which concluded that the use of cloth masks was not recommended in preventing the transmission of Covid-19. There is only 1 article that mentions the combination of several variations of cloth that are used globally for the production of cloth masks has the ability to protect the respiratory organs from the transmission of aerosol particles. Based on this, it was concluded that the use of cloth masks was less effective in preventing the transmission of Covid-19, but the use of cloth masks was much better than not wearing a mask at all.